AUDIO-VISUAL SYNKRETISM IN THE HISTORY OF ART AND EDUCATION - N. N. Telysheva (Russian State Vocational Pedagogical University, 2015)
The paper looks at the problems facing the art teachers and resulted, in the author's opinion, from separation of the content and functional side of the subject. The other problem is the lack of insight regarding social behavior, forms of consciousness and perception (including the spatial and temporal ones) underlying all sorts and forms of art. The paper demonstrates the interrelations between the history of arts and education history considered in terms of development and fixation of various forms of social consciousness. The audiovisual syncretism is regarded as the nature of perception and world reflection at specific historical stages of human knowledge and creativity development. Both the history of arts and education include the content and procedure related aspects. The whole history of pedagogy involves the procedure improvements (methods, means, forms, etc.) along the way «from integration to differentiation, and backwards»; and on the other side, it incorporates the invariable educational content. Likewise, throughout the history of arts we can trace the procedural aspect developments and the existence of the "eternal" content related to personality upbringing.